D Atherosclerotic inflammation imaging using 68ga-dotatate pet vs. 18f-fdg pet: a prospective clinical sudy with molecular and histological validation. (5th June 2017) - Tarkin, Jason M; Joshi, Francis R; Evans, Nicholas R; Chowdhury, Mohammed M; Figg, Nichola L; Shah, Aarti V; Starks, Lakshi T; Martin-Garrido, Abel; Manavaki, Roido; Yu, Emma; Kuc, Rhoda E; Grassi, Luigi; et al.
Abstract : Background: Inflammation drives atherosclerotic plaque rupture underlying most clinical events. While inflammation can be measured using 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET), 18F-FDG lacks cell-specificity and is unreliable for coronary imaging owing to myocardial signal spillover. Up-regulation of somatostatin receptor-2 (SST2) occurs in activated macrophages offering a novel inflammation imaging target. Methods: We comprehensively evaluated 68Ga-DOTATATE, a SST2 PET ligand, for imaging atherosclerosis. Target SSTR2 gene expression in macrophages and other immune cells were tested using population-based RNA-sequencing data. Patients with atherosclerosis (n=42) underwent 68Ga-DOTATATE PET imaging in a prospective head-to-head comparison with 18F-FDG. 68Ga-DOTATATE autoradiography, immunostaining and quantitative PCR were performed in macrophages and excised carotid specimens from patients who underwent PET imaging. Results: Target SSTR2 expression occurred exclusively in "pro-inflammatory" M1 macrophages, and no other cell type studied in vitro . In clinical imaging, 68Ga-DOTATATE mean of maximum tissue-to-blood ratios (mTBRmax) correctly identified culprit vs. non-culprit arteries in patients with acute coronary syndrome (median difference 0.69 [IQR 0.22 to 1.15], p=0.008) and transient ischaemic attack or stroke (median difference 0.13 [IQR 0.07 to 0.32], p=0.003). 68Ga-DOTATATE mTBRmax accurately predicted stable non-culprit coronary lesions with high-risk CT features (ROC AUC 0.86 [95% CI 0.80 to 0.92], p<0.0001), and correlated with Framingham risk score (r=0.53 [95% CI 0.32 to 0.69], p<0.0001) and vascular inflammation defined by 18F-FDG (r=0.73 [95% CI 0.64 to 0.81], p<0.0001). While 18F-FDG mTBRmax also differentiated culprit from non-culprit carotid lesions (median difference 0.12 [IQR 0.0 to 0.23], p=0.008) and high-risk from lower-risk coronary lesions (ROC AUC 0.76 [95% CI 0.62 to 0.91], p=0.002), myocardial 18F-FDG spillover rendered coronary 18F-FDG scans uninterpretable in 27 (64%) patients. In contrast, low myocardial 68Ga-DOTATATE binding allowed unimpeded coronary signal interpretation in all patients without the need for pre-scan fasting. Moreover, histological analysis confirmed specific binding of 68Ga-DOTATATE to SST2 receptors expressed by CD68-positive macrophages in excised carotid plaques. Carotid SSTR2 mRNA was highly correlated with both CD68 mRNA (r=0.93 [95% CI 0.49 to 0.99]; p=0.007) and in vivo 68Ga-DOTATATE PET signals measured from clinical images (r=0.89 [95% CI 0.28 to 0.99], p=0.02). Conclusion: We provide gene, cell, plaque and patient-level data, demonstrating that SST2 PET imaging using 68Ga-DOTATATE represents a macrophage-specific marker of atherosclerotic inflammation that outperforms 18F-FDG in the coronary arteries. Future research will explore the utility of 68Ga-DOTATATE inflammation imaging to classify high-risk patients for aggressive therapeutic intervention.